The Insurance Market in Ukraine: The State and Development Prospects - N. MELNYCHUK; S. ZALYUBOVSKA; YU. КОLUPAIEV (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2020)
In the current conditions of the economic development in Ukraine, an important place is occupied by the system of insurance relations. Although the insurance market in Ukraine is characterized by a low level of insurance culture, some insurers don’t fulfill their obligations, distrust of the population towards insurance companies, imperfection of state regulation mechanisms of the activity of these enterprises, low incomes of the population, etc.The research of the domestic insurance market shows that insurance itself provides the population with insurance protection against various insurance risks and is the most stable source of long-term investments. The existing insurance system in Ukraine is based mainly on principles that have demonstrated its inefficiency and do not meet the needs of the national economy. Urgency of this problem requires further study of the history of the insurance development as a whole, the identification of the development stages of insurance of the independent Ukraine and identification of a group of factors that influence the insurance market development.Growth of the entrepreneurial activity in the late nineteenth century and a stormy development of joint-stock companies were the beginning of agreements conclusion, definition of the rules of insurance, expansion of the reinsurance activity.Developmentoftheinsurancebusinesshasshownitsprofitability, therefore, in our country there is no significant decline in the number of insurance companies. In the competitive environment, insurance companies are increasingly expanding their range of insurance risks, seeking to increase their competitiveness. Insurance has a long history of formation, and research into historical aspects of the insurance development has begun with its evolution. Having analyzed literary sources, we have come to the conclusion that in Ukraine, the insurance development took place under the legal conditions that existed in the period of Kievan Rus and Tsarist Russia, and later in the USSR. Only the adoption of the Law on Insurance in 1996 made the domestic insurance market more developed and modern. Current state and four groups of factors that influence the insurance market development in Ukraine are analyzed. Prospects for the development of the insurance market in Ukraine are substantiated.